Impactors and the Impacted: Analytical Techniques to Identify and Understand the Impact Evolution of Extraterrestrial Materials - Forman, Lucy Victoria (Curtin University, 2017)
Impacts play a huge role in Solar System evolution. Signatures of the early phases of planetary compaction were identified in meteorites, which implied impacts were the driver for asteroid compaction. Traces of impacting projectiles have also been located at sites all over the world in impact ejecta layers. Here, ejecta from a catastrophic impact 65 Ma ago is examined to understand the process of global ejecta processing and dispersion.